NIH-supported implementation science and nutrition research: a portfolio review of the past decade - Vorkoper, Susan; Korn, Ariella R.; Maruvada, Padma; Nicastro, Holly L.; Shi, Scarlet (Frontiers in Public Health, 2023)
No funding sources to disclose. No conflicts of interest to disclose. This article does not contain any studies with human participants performed by any of the authors. This study does not involve human participants and informed consent was therefore not required. This article does not contain any studies with animals performed by any of the authors.The authors want to thank the NIH Implementation of Nutrition-related Programs, Practices, and Behaviors Implementation Working Group for their support and encouragement. In particular, we thank Ms. Karen Regan for her guidance in gathering data and Drs. April Oh and Alison Brown for their engagement in developing this portfolio analysis and their help in review.